ASSESSMENT OF INFANT AND YOUNG CHILD FEEDING PRACTICES OF CAREGIVERS IN IHIMA DISTRICT, OKEHI LOCAL GOVERNMENT AREA, KOGI STATE (FUDMA JOURNAL OF SCIENCES, 2025)
Optimal infant and young child feeding practices are crucial for improving health outcomes and reducing mortality rates among children under the age of two. However, inadequate nutrition during this critical period remains a leading cause of global malnutrition. This study assessed key indicators of infant and young child feeding practices in Ihima District, Okehi Local Government Area, Kogi State. A cross-sectional study was conducted among mothers and caregivers in Ihima District. Respondents were recruited using convenience sampling method. Data was collected on assessment of Infant and young child feeding practice using a validated semi-structured questionnaire. The interviewer-administered questionnaire obtained information on demographic characteristics, breastfeeding practices and complementary feeding practices based on WHO guidelines.  Data was analyzed using descriptive statistics and Chi-square on SPSS version 21, the p-values
Keywords: Infant and young child; Feeding practices; Breastfeeding; Complementary feeding; Pre lacteal feeding